2015
DOI: 10.1038/ncomms8062
|View full text |Cite|
|
Sign up to set email alerts
|

Ventral hippocampal afferents to the nucleus accumbens regulate susceptibility to depression

Abstract: Enhanced glutamatergic transmission in the nucleus accumbens (NAc), a region critical for reward and motivation, has been implicated in the pathophysiology of depression; however, the afferent source of this increased glutamate tone is not known. The NAc receives glutamatergic inputs from the medial prefrontal cortex (mPFC), ventral hippocampus (vHIP) and basolateral amygdala (AMY). Here, we demonstrate that glutamatergic vHIP afferents to NAc regulate susceptibility to chronic social defeat stress (CSDS). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
358
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(406 citation statements)
references
References 47 publications
33
358
1
1
Order By: Relevance
“…Moreover, in chronic stress models of depression, LTD in the NAc is disrupted in susceptible mice 64 and induction of LTD in the afferents to the NAc from the ventral hippocampus has a proresilient effect. 65 Taken together, the aforementioned results and our findings support the possibility that ketamine prevents potentiation of glutamatergic synapses in conditions of intense activation of glutamatergic inputs and oppose a loss of synaptic depression induced by, for example, chronic stress.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, in chronic stress models of depression, LTD in the NAc is disrupted in susceptible mice 64 and induction of LTD in the afferents to the NAc from the ventral hippocampus has a proresilient effect. 65 Taken together, the aforementioned results and our findings support the possibility that ketamine prevents potentiation of glutamatergic synapses in conditions of intense activation of glutamatergic inputs and oppose a loss of synaptic depression induced by, for example, chronic stress.…”
Section: Discussionsupporting
confidence: 76%
“…Nonetheless, the amygdala -hippocampus and amygdala -sgACC -PFC circuits proposed to underlie hyper-processing of negative stimuli in depression are characterized by changes in FC between regions analogous to those observed here in CPS mice (Disner et al, 2011). Using the common CSD protocol, it was demonstrated that increasing ventral hippocampus -nucleus accumbens (ventral striatum) synaptic transmission using optogenetic methods induced a further increase in social avoidance in CSD mice (Bagot et al, 2015). Whilst optogenetic stimulation of a pathway in stressed mice is clearly a different situation to endogenous pathway activity in stressed mice, one can nonetheless extrapolate from this finding to the present study, and hypothesize increased ventral hippocampus -ventral striatum connectivity in CPS versus control mice; this was not observed.…”
Section: Increases In Within-and Between-network Functional Connectivsupporting
confidence: 52%
“…Second, recent studies similarly involving BLA-to-AcbSh photoactivation and using similar frequency parameters (20Hz) have shown that this pathway promotes reward-driven rather than aversion-driven behaviors. For example, animals will learn to nosepoke for photoactivation of this pathway, albeit at relatively low rates (Britt et al, 2012; Stuber et al, 2011); and activation of this pathway reduces depression- and anxiety-related behaviors, and promotes social behavior in stress-induced animals (Bagot et al, 2015). In a clever demonstration of the impact this circuit on both appetitive and consummatory behavior, Prado and colleagues found that licks reinforced by optogenetic activation of excitatory terminals (that could be of prefrontal, BLA, and thalamic origin) in the AcbSh increased over 7 days the likelihood of licking in non-stimualtion periods, while simultaneously suppressing licking during the stimulation period itself (Prado et al, 2016).…”
Section: Discussionmentioning
confidence: 99%